How to improve success of technology projects in health and social care - Trisha Greenhalgh (Sax Institute, 2018)
Technologies are often viewed as the route to better, safer and more efficient care, but technology projects rarely deliver all the anticipated benefits. This is usually because they are too complex - and because the complexity is suboptimally handled. This article summarises a new framework to improve the success of technology projects: the nonadoption, abandonment, scale-up, spread and sustainability (NASSS) framework. The framework is based on a narrative systematic review and empirical work, and addresses the different domains in technology projects and how different aspects of complexity may be handled in each of them.